PEMROGRAMAN TRAINING UNIT VERTICAL REVOLVING HANDLING DEVICE DENGAN PROGRAMMABLE LOGIC CONTROL (PLC) - , PURWO AJI DWI SARJANTO, Ir. Tarmono., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
especial point Automation is a technology which apply machanical, electrical and computerizing system to operate, execute and handle a system, commonly manufacturing process. The aim of automation is to decrease loss time and to control sequences process. There are three points of automation, input, process and output. Programmable logic controller or PLC is one of the equipment automation as a processor in the automation process which is used to eliminate relays as a logical controller in a control proces system of automation. This study make a trainer is aimed to make the PLC application as a controll in automation process. The of this study especially in making PLC program which know as ladder diagram. is There are some methods used in this study. The first colleting information from literature and learning from person who competent in this case. The second is making the trainer kit, and the last in analyzing the process which will be executed to make PLC program. this rep As the result, ort have conclusion, they are the trainer kit has been successfully made, all processes are running very well and the PLC program can be applied at the trainer kit.